Understanding emotions - Andrews, Elizabeth, 1996- (2023)
Emotions become more complex as children grow up. Understanding what and why they are feeling certain ways will help readers form healthy relationships. This title explains key emotions with clear, easy-to-read text and real-world examples. QR Codes in the books give readers access to book-specific resources to further their learning.
"4D book!"
Includes index.
Ages 3-6
Keywords: Emotions in children -- Juvenile literature; Emotions -- Juvenile literature; Emotions; Emotions in children; Juvenile works